New Insights into Pediatric Pulmonology - Bentur, Lea; Bar-Yoseph, Ronen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Children with pulmonology issues have always introduced challenges for pediatricians. This Special Issue provides a platform for researchers and clinicians to discuss the novel methods of functional assessment, new insights into exercise physiology, the effect of maturation and puberty on pulmonary parameters, the translational aspects of overweight and obesity, the evaluation of active rehabilitation in pediatric pulmonology, long-term and post-COVID-19 illnesses, the pediatric origin of adult diseases, etc.